MULTIPLEX PCR TO DETECT Brucella AND Leptospira SPECIES IN SPIKED MILK SAMPLES - R. Manju Priya; M. Ananda Chitra (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Brucellosis and leptospirosis are zoonotic diseases and cause much economic losses in livestock by causing abortion, stillbirth and infertility. Both organisms are excreted in milk and thus increasing the risk of infecting other animals and human. Early detection of organisms is desirable for effective treatment and control of diseases. In this study, multiplex PCR was attempted to detect Brucella and Leptospira species in spiked milk samples. Brucella genus specific primers were designed and E1E2 primers that target only pathogenic leptospires were used to yield the amplicon of 230bp and 571bp respectively. CTAB and lysis methods were used to extract DNA from spiked milk samples and found that lysis method is more sensitive than CTAB method in detecting both organisms. CTAB method could detect both organisms in 104 per ml but lysis method detected both organisms in 103 per ml. This multiplex PCR can also be used to detect these bacteria in other clinical samples such as aborted fetus, placenta, uterine discharges, urine and blood.